Influence of Biochar Fortified with Fungi (Termitomyces) on Carbon Stock, Flux, and Yield of Groundnut - Wakili, Habib Dahiru; Abdulsalam, Khalid; Wakili, Habib Hafsah (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
The study was conducted to investigate carbon stock, flux, and sequestration potential as well as the response of groundnut (yield) to different fortification approaches. A greenhouse experiment was conducted using four treatment combinations, fortified biochar with T. albuminosus (B + T), biochar (B), T. albuminosus, and control laid in a Complete Randomized Design (CRD). The result showed increased carbon sequestration, stock, and a subsequent decrease in carbon emission in treatment B + T relative to other treatments. Untreated samples recorded the lowest values with 3.69 g kg-1 sequestered carbon 24.97 kg ha- stock 4.92% carbon emission and a net flux of -20.70. The highest groundnut yield was also recorded in the B + T treatment with a value of 1131.10 kg ha-1. However, biochar treatment recorded the highest biomass and stover yield 5.62 t ha-1 and 3.82 t ha-1 respectively. In conclusion, the Fortification of biochar with T. albuminosus proved efficient in improving carbon sequestration, increasing carbon stock, and reducing emission as well as other nutrients in soils under cultivation. Also, using B + T as an amendment under optimal growth conditions is recommended for better groundnut production. The study's constraints lie in its execution within controlled greenhouse settings, potentially limiting its applicability to real-world field conditions. Thus, caution should be exercised when extending these findings to field applications, ensuring the validation of the approach's effectiveness.